Community Norms about Suppression of HIV/AIDS Prejudice and Perceptions of Stigma by People with HIV/AIDS - Miller, Carol T. (2011)
We investigated the relationship between reports by 203 people with HIV/AIDS in New England communities about their experiences with stigma and reports by 2,444 randomly selected residents of those same communities about their motivation to control HIV/AIDS prejudice. Multi-level regression analyses revealed that the disclosure concerns of participants with HIV/AIDS were lower in communities in which residents were motivated by personal values to control HIV/AIDS prejudice, and were higher in communities in which residents were motivated by social pressure to control HIV/AIDS prejudice. Reported experiences with discrimination and exclusion were unrelated to these community motivations. These results suggest that the realities of the communities in which stigmatized people live shape their perceptions of stigmatization.